2008
DOI: 10.1080/15205430802368621
|View full text |Cite
|
Sign up to set email alerts
|

The First-Person Effect and Its Behavioral Consequences: A New Trend in the Twenty-Five Year History of Third-Person Effect Research

Abstract: The perceived effect of the media on the self when compared to others has been adequately established over the last 25 five years. Rather than a third-person effect where individuals perceive a greater effect for self than others, first-person effect perceptions, where individuals perceive a greater effect for self than others, have been considered by scholars recently. Findings indicate support for first-person perceptions. However, research is limited and the behavioral consequences of first-person perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 62 publications
(89 reference statements)
2
35
1
1
Order By: Relevance
“…This meta-analysis found that key moderators of TPP were desirability of the message influence (i.e., messages that are not socially desirable [e.g., pornography] are perceived to have more of an effect on others), vulnerability of others (e.g., children might be perceived to be more affected by television violence than adults), similarity of self to others (i.e., when the sociodemographics of self and others are more similar, TPP is reduced), and likelihood of the other to be an audience member of media content (e.g., adolescents might be perceived to be more affected by music videos than adults, because adolescents are more likely to be the audience for such content). In contrast to TPP, first-person perception (FPP) occurs when an individual perceives that he or she will be affected by media content more than someone else (Golan & Day, 2008). FPP is generally understood to occur with prosocial media (e.g., a public-service announcement about practicing safe sex might be perceived to have more of an effect on oneself compared to others; Duck, Terry, & Hogg, 1995).…”
Section: Media Bias and Third-person Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…This meta-analysis found that key moderators of TPP were desirability of the message influence (i.e., messages that are not socially desirable [e.g., pornography] are perceived to have more of an effect on others), vulnerability of others (e.g., children might be perceived to be more affected by television violence than adults), similarity of self to others (i.e., when the sociodemographics of self and others are more similar, TPP is reduced), and likelihood of the other to be an audience member of media content (e.g., adolescents might be perceived to be more affected by music videos than adults, because adolescents are more likely to be the audience for such content). In contrast to TPP, first-person perception (FPP) occurs when an individual perceives that he or she will be affected by media content more than someone else (Golan & Day, 2008). FPP is generally understood to occur with prosocial media (e.g., a public-service announcement about practicing safe sex might be perceived to have more of an effect on oneself compared to others; Duck, Terry, & Hogg, 1995).…”
Section: Media Bias and Third-person Perceptionmentioning
confidence: 99%
“…This feature of online news provides opportunity for user engagement with a news source as well as with other readers of the site. In best cases, this user participation can result in an online conversation about the news (Glaser, 2008), while in worst cases it might result in ''cacophonous shouting matches'' among online readers (Ingram, 2010, {1). As a result, news organizations continue to wrestle with how to monitor and regulate user comments on news websites (Brisbane, 2010;Perez-Pena, 2010;Pitts, 2010;Swidey, 2010).…”
Section: User Comments and Online Newsmentioning
confidence: 99%
“…This false premise was used because supporting censorship of negative media is one of the most common outcomes associated with the third-person effect (Golan & Day, 2008), and movie ratings are essentially a form of censorship. Moreover, giving participants an outcome to contemplate is more likely to result in stronger, more evaluative attitudes (Bradburn & Sudman, 2004), than asking about attitudes with no potential outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…That is, the urge to report that others are more influenced by the media is rooted in a tendency for people to present themselves in a positive light. The third-person differential would therefore become smaller in size or even reversed in direction when the media influence concerned is desirable (e.g., Duck & Mullin, 1995;Golan & Day, 2008;Gunther & Mundy, 1993;Hoorens & Ruiter, 1996;Jensen & Hurley, 2005).…”
Section: Message-attitude Congruence and The Third-person Perceptionmentioning
confidence: 98%